Talent Identification and Development in Youth Sports - Kelly, Adam Leigh; Jiménez Sáiz, Sergio L.; Santos, Sara; Lorenzo Calvo, Alberto (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are delighted to share our Special Issue on Talent Identification and Development in Youth Sports. In 2020, the editorial team had several informal discussions about the growing interest from researchers and practitioners in these disciplines, and subsequently wanted to create a platform to help advance this field of literature. Following these conversations, we decided to use the Personal Assets Framework (Côté et al., 2014, 2016) to outline our objectives and the potential research topics for our Special Issue. In doing so, it was hoped that the studies included can inform evidence-based youth sport policies and athlete development programmes. Submissions were encouraged from a diverse range of quantitative and qualitative research methods to examine the current context of talent identification and development in youth sports, as well as reviews to synthesise expert knowledge within these disciplines. In light of the articles that have been included within our Special Issue, we believe our initial aims of progressing the talent identification and development literature have been achieved, and now hope that the research presented can be utilised by key stakeholders (e.g., administrators, coaches, parents, practitioners) and organisational structures (e.g., national governing bodies, professional clubs, recreational teams, youth sport associations) to create more appropriate youth sport settings.